Past And Current Development Of Two-Phase Modeling Of Polypropylene In Gas Phase Fluidized Bed Reactor : A Review - Mohd Farid, Bin Atan; Mohd Azlan, bin Hussain; Nazeri, Bin Abdul Rahman (2018)
Polypropylene which is also known as PP is one of the polyolefins which is widely used in several types of industries, for instance, aeronautics, automotive, packaging, textiles etc. The demand for this said polyolefins continues to increase annually due to its chemical and physical properties in term of its density, toughness, flexibility, thermal expansion, etc. With regards to this high demand, the production rate of this said polyolefin need to be improved in order to ensure the global demand is catered accordingly without any shortage in term of its supplychain. To increase the production rate and concurrently to improve its chemical and physical properties, the implemented mathematical model needs to be revised and improved. Thus, this review article is focusing on reviewing the past and current development of the two-phase mathematical model which has been implemented recently in simulating the polymerization process of polypropylene in the gas phase fluidized bed reactor. This review consists of reviewing several aspects of the implemented two-phase mathematical model which are the reaction mechanism, the kinetic modeling, the mass, and energy balance modeling, and lastly, the output variables predicted from this said mathematical model such as the production rate, the average molecular weight, the polydispersity index, the temperature of the fluidized bed, concentration of monomer, the temperature of the different phases, melt flow index or melt index, etc. In addition, assumptions proposed by previous studies are also reviewed and discussed. Finally, this review is concluded by proposing the elements which can be embedded to improve the quality of the output variables predicted by this said mathematical model.